Teaching Young Adult Literature Today: Insights, Considerations, and Perspectives for the Classroom Teacher (second edition), Young Adult Nonfiction: Gateway to the Common Core, and Teaching Young Adult Literature - Terri Suico (Study and Scrutiny, 2019)
A review of Teaching Young Adult Literature Today: Insights, Considerations, and Perspectives for the Classroom Teacher (second edition), Young Adult Nonfiction: Gateway to the Common Core, and Teaching Young Adult Literature: Integrating, Implementing, and ReImagining the Common Core by Judith A. Hayn and Jeffrey S. Kaplan.